'Brightening their leisure hours'? The experiment of BBC Women's Hour, 1923–1925. Issue 2 (23rd February 2020) - Murphy, Kate
ABSTRACT: On 2 May 1923, the newly established BBC, launched Women's Hour, a daily bespoke programme aimed at its female audience produced by Ella Fitzgerald, a former Fleet Street journalist. In December 1923 a Women's Advisory Committee (WAC) was established to represent women's interests at the BBC with eminent members who included the Chairman of the National Federation of Women's' Institutes, Lady Denman; the actress Dorothea Baird and the physician Elizabeth Sloan Chesser. The WAC, working with Fitzgerald and other BBC officials, introduced into Women's Hour an innovative range of programme ideas. It also prompted a debate about the premise of the programme, whether it should be about domesticity or provide escapism from the 'common task' of housework. In addition the WAC challenged the Women's Hour name. Through a consideration of the programme and the WAC, both of which were short-lived, this article explores how the BBC sought to address its female audience in the early 1920s.